2018
DOI: 10.24114/jpb.v7i3.10123
|View full text |Cite
|
Sign up to set email alerts
|

Profil Keterampilan Literasi Sains Siswa di Salah Satu Sekolah Swasta di Karanganyar

Abstract: This study aims to determine the profile of students' literacy skills in one of the private high schools in Karanganyar. This study uses a survey method. The study population was all high school students of class X, XI, and XII MIA. The sampling technique uses stratified proportional random sampling with a total sample of 45 students. Science literacy skills are measured using the 2015 Program for International Student (PISA) test with indicators developed by Gormally. The results showed that in general, the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
13

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 0 publications
1
14
0
13
Order By: Relevance
“…Other undergraduate students do not understand the purpose of the problem. These results are in line with research that shows that the cause of students' difficulty in solving story problems, one of which is students cannot interpret the intent of the problems [15].…”
Section: ) Apply the Concept Of Acid-base To Solve The Problem Of Thsupporting
confidence: 91%
See 2 more Smart Citations
“…Other undergraduate students do not understand the purpose of the problem. These results are in line with research that shows that the cause of students' difficulty in solving story problems, one of which is students cannot interpret the intent of the problems [15].…”
Section: ) Apply the Concept Of Acid-base To Solve The Problem Of Thsupporting
confidence: 91%
“…Observation and learning questionnaire to determine the learning process during the lecturer teaching in class. Criteria for assessment of science literacy undergraduate students use the following categories [14], [15]:…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…How to graph the correct data can be exemplified by the teacher as a facilitator through the virtual laboratory features in the portal "home learning". Graphs in scientific literacy can be understood by students by interpreting certain data by making graphs of various types of graphs based on their usefulness and data graphs are a form of scientific claims in supporting quantitative data in scientific literacy (Gormally et al, 2012;Rahmadani et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…Several studies conducted in Indonesia also revealed the students' weaknesses in mastering science literacy (Angraini, 2014;Kharizmi, 2015;Novika, 2016;Rahmadani, et al, 2018). Students' abilities are only in the nominal category (initial) (Fitriani, 2012; Odja & Payu, 2014).…”
Section: Introductionmentioning
confidence: 99%